Physiological responses and adaptations to exposure from moderate to extreme altitude: A case study of the youngest Malaysian climber to scale Mt. Everest / Adam Feizrel Linoby … [et al.] - Linoby, Adam Feizrel; Nias, Mohd Azmi; Ahmad, Badli Esham; Zaki, Sufyan; Canda, Roger; Sariman, Hanifa; Azam, Zulkhairi; Amat, Aripin (2013)
The intense environmental conditions at the summit of Mt. Everest put human physiology near the limit of tolerance. The immediate (acute) effects of severe oxygen deprivation of extreme altitudes related to the human response and the adaptations to prolonged exposure (chronic) are complex. Mohd Nasuha Shamsudin, the youngest Malaysian climber to scale Mt. Everest was selected for the case study. Analysis of both acute and chronic physiological responses and his self-reported health related symptoms during his expedition to summit of Mt. Everest was studied. The purpose of this study was to describe the respondent's responses and adaptation to his cardiovascular, respiratory, bioenergetics, physical performance as well as the health problems in different level of altitude. The finding, found several primary symptoms of hypoxia including headache, nausea, dizziness, insomnia, shortness of breath upon exertion, persistent rapid pulse, excessive flatulence and general fatigue upon reaching to high altitude. The respondent also reported common problem at high altitude including loss of appetite, dehydration and severe 'khumbu cough '. Useful information was gained based on the climber's self-reported measurement and experience in relations to the extreme altitude acclimatization and sickness and the physiological implication at an altitude.